The environmental effects of monocentric urban spatial structure with city-level evidence from China - Yanchun Yi; Ji Qi; Yinling Liu; Xinjing Wang; Tuofu Jin (Scientific Reports)
Abstract Spatial structure adjustment has become one of the important means to improve urban environments. However, what is the impact of urban spatial structure on environment? Research on this issue will be beneficial for the improvement of urban environmental quality. Based on panel data from 285 cities at China’s city level from 2006 to 2020, this paper empirically studies the effects of urban spatial structure on environment and explores the potential influencing mechanisms. The findings are as follows: (1) Monocentric urban spatial structure increases environmental pollution. (2) The influencing mechanisms mainly include private transportation, population agglomeration, and natural purification. (3) The impact of urban spatial structure on pollution exhibits a positive “U”-shaped nonlinear relationship, with an initial decrease followed by an increase as the degree of monocentric dominance in cities increases.